THE FORMATION OF TRANSASIAN AND EURO-ASIAN TRANSPORT ROUTES AS A PREREQUISITE FOR THE FORMATION OF A NEW QUALITY OF CULTURAL AND HISTORICAL PROGRESS - Pokotilov, A. A. (Science and Transport Progress, 2006)
Theoretical substantiation is provided to objective and subjective factors of creation of trans-Asian and Euro-Asian mainlines, as a pre-condition of establishing new quality of cultural and historical progress.